High-Tc Superconducting YBa2Cu3O7-δ Films and YBa2Cu3O7-δ/PrBa2Cu3O7-δ Superlattices Deposited by Laser Ablation - J. Levoska; S. Leppävuori (Active and Passive Electronic Components)
High Tc superconducting YBa2Cu3O7-d thin films and YBa2Cu37-δ/PrBa2Cu3O7-δ superlattices with various periods and layer thicknesses were deposited by laser ablation on SrTiO3 (100) single crystal substrates using an XeCl excimer laser (λ = 308 nm). The structure of the films was studied by SEM/EDS and X-ray diffraction. The films and superlattices deposited in an in situ process were epitaxial with the c-axis perpendicular to the substrate surface and the a- and b-axes parallel with the SrTiO3 [100] or [010] directions. The electrical properties were studied by measuring the current-voltage characteristics, resistivity and critical current. For the in situ deposited YBa2Cu3O7-d films the zero resistivity temperature was 87 to 90 K and the critical current at 77 K was above 2 × 106 A/cm2. For the films deposited at room temperature and post annealed under in situ deposition conditions, the critical temperature was the same, but the critical current was 0.5 × 106 A/cm2.